2 - La Crise des Finances publiques et la Dénationalisation de l’Etat: le cas du Mali : by Bernard Founou-Tchuigoua - Bernard Founou-Tchuigoua (Africa Development, 1989)
Mali is rightly considered as one of the African countries faced with a spectacu- lar developmental and fiscal crisis as evidenced by the withdrawal of the state from public investment, as well as the degradation of major services such as education, health and infra- structure. Conventional theory denotes three functions to public finance namely financing of state activities, redistribution of revenue particularly to disadvantaged sectors of society and regulating the economy through mechanisms such as the banking system. Contrary to its univer- sal and egalitarian assumptions, an examination of international public aid in which technical assistance plays a strategic role underscores the hierarchical nature of relations between various states. To the three functions listed above, a fourth and significant function of public finance will have to be added - the reproduction of unequal relations between the center and the peri- phery. Similarly the function of redistribution varies in the two poles. In the periphery where the system of social security is not developed, there is perverse redistribution. Public finance serves to redistribute resources taken mostly from the poor and middle class to a minority class, the top administration. It is essentially through private accumulation and job-creation for the educated youth that the class in power reproduces itself. In Africa, and Mali is a good case in point, the capacity for self -adjustment of the imbalances of state budget is missing. Hence, attempts at balancing the budget through the reduction of the remuneration of labour in order to increase the potential benefits of investors result in under employment and impoverishment of the masses. At the root of the current fiscal crisis in Mali and some which have a dialectical relationship with it include, population increase, urbanization, the emergence of the private sector, the alarming educational crisis and the debt crisis. The neo-liberal responses to these multifarious crisis has initiated a process of "denationalization of the State".